Multibeam bathymetry raw data (EM 120 echosounder entire dataset) of RV SONNE during cruise SO236 - Betzler, Christian; Lindhorst, Sebastian; Wunsch, Marco (PANGAEA, 2022)
Multibeam bathymetry raw data using the ship's own Kongsberg (Simrad) EM 120 multibeam echosounder was almost continuously recorded during RV SONNE cruise SO236. Data was recorded on 20 days between 2014-08-09 and 2014-08-29. This dataset contains various surveys at the Maldives islands. The approximate average depth of the entire dataset is around 1400m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. However, data analysis of the multibeam raw data revealed that SVP has been changed a few times during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area "Data management and Digitalization" (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather moderate since the gridded hillshade data showed some obstacles. During the cruise the multibeam system was considered not working properly (SO236 was the last scientific voyage of RV SONNE). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).
Keywords: Bathymetry; Multibeam Echosounder